Die Diätenfrage Zum Abgeordnetenbild in Staatsrechtslehre und Politik 1900-1933 - Urban, Nikolaus (Mohr Siebeck, 2003)
Remuneration for Members of Parliament. The Image of Members of Parliament in Constitutional Law and Politics from 1900 to 1933.
PublicationDate: 20220817
Keywords: Rechtsgeschichte -- Politik -- Staatsrechtslehre -- Allgemeines -- Array